2012
DOI: 10.5402/2012/748734
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Some Manfacturing Parameters on Machining of Extruded Al-Al2O3 Composites

Abstract: A wide range of particulate metal matrix composites (PMMCs) of alumina and aluminum powders was formed using powder metallurgy techniques followed by extrusions at various extrusion ratios. The machining characteristics of the extruded PMMC were investigated. Results showed significant effects of weight fractions of reinforcement and extrusion ratios on tool wear and surface integrity of machined surface. The wear rate of cutting tool decreased rapidly with increasing the cutting parameters: cutting speed, fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…They presented that the increasing of Al 2 O 3 nanoparticles to copper matrix enhance, wear resistance, and microhardness. Additionally, they concluded that the wear resistance and microhardness are enhanced by the addition of increasing Al 2 O 3 weight fraction [43,44]. Since mechanical alloying is high energy milling process, numerous number of milling parameters can influence the process [45].…”
Section: Introductionmentioning
confidence: 99%
“…They presented that the increasing of Al 2 O 3 nanoparticles to copper matrix enhance, wear resistance, and microhardness. Additionally, they concluded that the wear resistance and microhardness are enhanced by the addition of increasing Al 2 O 3 weight fraction [43,44]. Since mechanical alloying is high energy milling process, numerous number of milling parameters can influence the process [45].…”
Section: Introductionmentioning
confidence: 99%
“…However, use of the coated inserts reduces too wear and hence increases productivity [21] [22] [23]. Further, use of PCD inserts results superior surface texture and increases productivity [24] [25].…”
Section: Introductionmentioning
confidence: 99%
“…A high specific stiffness and strength are the most important properties of aluminum alloys strengthened and reinforced with ceramic particulates. [1][2][3] Al-metal matrix composites (MMCs) with previous properties can be used in long-term applications, such as robots, aerospace, automotive engine, high-speed machinery, high-speed rotating shafts and metals reflect microwaves, in which saving weight is an important feature. [4][5][6] Methods of fabrication of MMCs can be divided into two main sets: (a) solid state methods (such as, mechanical milling, powder metallurgy, etc.)…”
Section: Introductionmentioning
confidence: 99%